The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/molbev/msz224
|View full text |Cite
|
Sign up to set email alerts
|

Along the Indian Ocean Coast: Genomic Variation in Mozambique Provides New Insights into the Bantu Expansion

Abstract: The Bantu expansion, which started in West Central Africa around 5,000 BP, constitutes a major migratory movement involving the joint spread of peoples and languages across sub-Saharan Africa. Despite the rich linguistic and archaeological evidence available, the genetic relationships between different Bantu-speaking populations and the migratory routes they followed during various phases of the expansion remain poorly understood. Here, we analyze the genetic profiles of southwestern and southeastern Bantu-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 50 publications
(72 reference statements)
16
50
0
Order By: Relevance
“…1 ). Similarly low levels of local group admixture have been noted for Bantu speakers from Malawi 16 and Mozambique 21 . A recent attempt to reconstruct the route of Bantu migration across central Africa concluded that populations from Angola were the best source of Bantu speakers for east and south African Bantu speakers, and suggested a westerly route of Bantu-speaker migration via Angola 9 .…”
Section: Insights Into Migration and Admixturementioning
confidence: 56%
“…1 ). Similarly low levels of local group admixture have been noted for Bantu speakers from Malawi 16 and Mozambique 21 . A recent attempt to reconstruct the route of Bantu migration across central Africa concluded that populations from Angola were the best source of Bantu speakers for east and south African Bantu speakers, and suggested a westerly route of Bantu-speaker migration via Angola 9 .…”
Section: Insights Into Migration and Admixturementioning
confidence: 56%
“…In addition, the extent of the gene-flow also varies considerably between the SEB groups clearly differentiating them from one other. For example, the Khoe-San ancestry levels vary from >20% in the South African Tswana and Sotho to only around 3% in the Chopi and Tswa from south Mozambique, whereas central and north Mozambican populations, Zambian and Malawian populations have no admixture signals with Khoe-San ( 16 , 37–39 , 46 ) ( Fig. 1 ).…”
Section: Admixture Of Bantu-speakers With Resident Hunter-gatherer Populationsmentioning
confidence: 99%
“…The intensity of this sex bias increases from North to South, possibly indicating changes in social interactions between immigrating groups and autochthonous peoples over time ( 35 ). Such changes in interactions are also implied by the varying levels of Khoisan-related ancestry detectable in modern-day Bantu-speaking populations of southern Africa: populations from Malawi do not show any evidence for Khoisan-related ancestry ( 14 ), and populations from southern Mozambique show only low levels of such ancestry [4–5% maximum ( 43 )]. This is in contrast to populations such as the Kgalagadi and Tswana from Botswana with 33–39% and 22–24% Khoisan-related ancestry, respectively ( 29 , 36 ), or the Sotho, Xhosa and Zulu from South Africa with between ~10–24% Khoisan-related ancestry ( 43 , 44 ).…”
Section: Admixture With Immigrating Food-producing Populationsmentioning
confidence: 99%
“…Such changes in interactions are also implied by the varying levels of Khoisan-related ancestry detectable in modern-day Bantu-speaking populations of southern Africa: populations from Malawi do not show any evidence for Khoisan-related ancestry ( 14 ), and populations from southern Mozambique show only low levels of such ancestry [4–5% maximum ( 43 )]. This is in contrast to populations such as the Kgalagadi and Tswana from Botswana with 33–39% and 22–24% Khoisan-related ancestry, respectively ( 29 , 36 ), or the Sotho, Xhosa and Zulu from South Africa with between ~10–24% Khoisan-related ancestry ( 43 , 44 ). Such changes in social interactions between immigrating Iron Age agropastoralists and resident Khoisan-speaking populations might also explain variable patterns of click borrowing in Bantu languages ( 18 , 45 ).…”
Section: Admixture With Immigrating Food-producing Populationsmentioning
confidence: 99%